Aldosterone contributes to hypertension in male mice inducibly overexpressing human endothelin-1 in endothelium. Issue 9 (25th September 2021) - Berillo, Olga; Coelho, Suellen C.; Mahjoub, Nada; Offermanns, Stefan; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Mechanisms of blood pressure (BP) regulation by endothelin (ET)-1 produced by endothelial cells are complex and remain unclear. Long-term exposure to human ET-1 (hET-1) in mice inducibly overexpressing hET-1 in the endothelium (ieET-1) caused sustained BP elevation. ET-1 has been shown to stimulate the release of aldosterone. Whether aldosterone plays a role in hET-1 overexpression-induced BP elevation and vessel injury is unknown. Method: Nine- to 12-week-old male ieET-1 mice and control mice expressing a tamoxifen-inducible Cre recombinase (CreER T2 ) in the endothelial cells (ieCre) were treated with tamoxifen for 5 days and studied 3 months later. Results: Endothelial hET-1 overexpression increased plasma aldosterone levels, which was reversed by 2-week treatment with atrasentan, an endothelin type A receptors blocker. Aldosterone synthase and cryptochrome 2 adrenal cortex mRNA expression was decreased in ieET-1 mice. Two-week treatment with eplerenone, a mineralocorticoid receptor antagonist, reduced systolic BP by 10 mmHg in ieET-1 mice during rest time. Saline challenge-induced sodium excretion and renal cortex thiazide-sensitive sodium-chloride cotransporter mRNA expression were decreased in ieET-1 mice. The sensitivity of mesenteric arteries to contraction by norepinephrine was increased in ieET-1 mice, and was abrogated by eplerenone treatment, whereas sensitivity of endothelium-independent relaxation responses to sodium nitroprusside was enhanced. Resistance artery remodeling was reduced in eplerenone-treated ieET-1 vs. ieET-1 and ieCre mice. Conclusion: These results demonstrate that aldosterone contributes to BP elevation and vascular norepinephrine sensitivity and remodeling caused by hET-1 overexpression in endothelium in mice.